Religious holiday effect on Borsa Istanbul - (:unkn) unknown (ACRN Oxford Ltd., 2018)
Problem/ Relevance: Calendar anomalies have been studied by a number of articles especially in the last two decades, which is considered against the efficient market hypothesis. Mostly, anomaly researchers have examined the holiday effect, the day of the week effect, the month effect, the year effect, and the holy days effect in order to investigate the particular time period for abnormal returns. The holiday effect is regarded as a well-organized calendar effect in stock markets and it has significant theoretical background Research Objective/ Questions: This study attempts to analyze the effect of the Religious Holiday - the feast of Ramadan and the feast of Sacrifice- on sectoral indices returns at the Borsa Istanbul for the time period between 1997-2015. BIST100, BIST30 and 23 sectoral indices are considered for this study. Their return performances' at time Day-3 (three days before religious holidays), Day-2 (two days before religious holidays), Day-1 (one day before religious holidays), Day+1 (one day after religious holidays), Day+2 (two days after religious holidays) and Day+3 (three days after religious holidays) are studied. Methodology: In order to compare the results of both regression analysis and non-parametric tests, they were analyzed together. Mann-Whitney, Kruskal-Wallis, and Wilcoxon Rank tests were used for non-parametric tests. Major Findings: The analysis shows that average return of Day-2 is better than the other days. 12 sectoral indices display positively statistically significant results on that day. Returns of BIST Real Estate, BIST Services, BIST Transportation were positive and statistically significant at the 10% level; returns for BIST Electricity, BIST Industrial, BIST Inv. Trust, BIST Tourism, BIST Wood, Paper and Print were positive and statistically significant at the 5% level; BIST Food & Beverage, BIST Non-Material Products, BIST Leasing and BIST Textiles were positive and statistically significant at the 1% level. Implications: This study indicated that there is religious holiday effect in the BIST for some indices, which have highest average returns at Day-2. This study aimed to contribute to the efforts of academicians who study this field, and investors for their investment strategies, which may now be developed by analyzing the volatility of these indices at those time periods. © 2018 ACRN Oxford Ltd.. All rights reserved.
Keywords: Behavioral finance; Borsa Istanbul; Islamic finance; Religious holidays